2021
DOI: 10.1155/2021/3765046
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Asphericity and Higher-Order Aberrations after FS-LASIK and Trans-PRK for Myopia

Abstract: Objective. To compare the corneal asphericity and higher-order aberrations (HOAs) of femtosecond laser-assisted in situ keratomileusis (FS-LASIK) with Smart Pulse Technology (SPT) assisted transepithelial photorefractive keratectomy (Trans-PRK) for myopia and myopic astigmatism correction. Methods. This prospective study analyzed 88 eyes of 44 patients treated with FS-LASIK and 64 eyes of 32 patients treated with Trans-PRK. All eyes had low to moderate myopia with or without astigmatism (spherical equivalent (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…20 Studies report that increased anterior corneal surface HOAs after photorefractive keratectomy, LASIK, and laser-assisted subepithelial keratectomy are mainly from increased spherical and coma aberrations. [21][22][23] A notable finding in our study was unchanged spherical aberration. However, trefoil and coma increased much more than spherical aberration after surgery.…”
Section: Discussionsupporting
confidence: 61%
“…20 Studies report that increased anterior corneal surface HOAs after photorefractive keratectomy, LASIK, and laser-assisted subepithelial keratectomy are mainly from increased spherical and coma aberrations. [21][22][23] A notable finding in our study was unchanged spherical aberration. However, trefoil and coma increased much more than spherical aberration after surgery.…”
Section: Discussionsupporting
confidence: 61%
“…Corneal asphericity at the anterior corneal surface is negative and increases from the center to the periphery. [14] Esraa El-Mayah et al previously suggested that the spherical aberration at 6.0 mm is affected by the ablation pro le method, but the Q-value at 8.0 mm is a parameter that could predict ablation volume or ablation depth relatively independently of ablation pro le; [15] as such, the measurement of the Q-value in the 8 mm zone was investigated in our study. In LASIK, monovision is a method of presbyopic correction, in which one eye is corrected for distance vision and the other eye for near vision, and this procedure is based on Q factor modulation.…”
Section: Discussionmentioning
confidence: 90%
“…PRK was chosen as the corneal procedure given that the patient had occupational risk for trauma. Furthermore, some studies suggest that PRK induces fewer aberrations than laser in situ keratomileusis (LASIK), which is an important consideration in a patient who already has two IOLs [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%